Eksplorasi Potensi Bakteri Entomopatogen di Areal Tanaman Perkebunan Provinsi Kalimantan Utara - Abdul Rahim; Roslina Roslina; Nurmaisah Nurmaisah; Muh. Adiwena (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Plantation areas have the potential as a source of biological agents for entomopathogenic bacteria. This study aims to determine the potential of entomopathogenic bacteria from various locations in plantation crop cultivation areas, and compare their potential in North Kalimantan Province. This study carried out soil sampling, bacterial isolation, and selection of entomopathogenic bacteria using insect baits. This type of research uses a survey method on the potential of entomopathogenic bacteria. The survey was conducted at three plantation crop cultivation locations, namely coffee cultivation areas in Malinau, cocoa in Sebatik, and oil palm in Sebuku. The potency is distinguished based on the number and macroscopic characteristics of the bacterial isolate colonies obtained from each location. Furthermore, selection was carried out through testing, namely comparing bacterial isolates with a dilution of 10-1, stock, and control. Analysis of survey results using descriptive analysis and potential testing using t-test. The results showed that there were 13 bacterial isolates, and the coffee cultivation area in Malinau had the highest bacterial isolates. The selection results found 7 (seven) bacterial isolates that had the potential to be entomopathogenic bacteria, and coffee cultivation locations in Malinau had a higher number of isolates that had the potential to be entomopathogenic compared to other locations. However, isolate ST6-4U2 at dilution 10-1 from soil in the oil palm plantation area in Sebuku has the highest virulence potential as an entomopathogenic bacteria.